Prevalence of fibromyalgia in Egyptian patients with systemic lupus erythematosus and its impact on health-related quality of life - Samar Tharwat; Rahma A. Elziaty; Fatma Hamdy; Abdelrahman Mohamed Elsayed; Esraa A. Talaat; Enas S. Zahran (Advances in Rheumatology, 2026)
Abstract Background Fibromyalgia (FM) is a rheumatic disorder characterized by widespread persistent pain, hyperalgesia, and allodynia. Objectives The aim of this study was to assess the prevalence of FM among Egyptian patients with systemic lupus erythematosus (SLE) and its effect on their health-related quality of life (HRQoL). Materials and methods This cross-sectional analytical multicenter study was conducted on 550 Egyptian SLE patients. The patients’ sociodemographic characteristics, clinical and therapeutic data, and sleeping patterns were collected. SLE disease activity index (SLEDAI) was assessed. We employed the 2016 revisions to the 2010/2011 FM diagnostic criteria to determine the presence of FM and the patients administered the Short-Form Health Survey-36 (SF-36). Results The mean (SD) age was 32.72 (9.90) years, and 91.3% were female. Of 550 Egyptian SLE patients, 119 (21.6%) fulfilled the diagnostic criteria of FM. The FM group was statistically significantly associated with higher age ( P = 0.001), body mass index (BMI) ( P = 0.008), longer SLE duration ( p < 0.001), and higher scores of SLEDAI ( p < 0.001). Also, living alone ( p < 0.001), chronic psychiatric disease ( p = 0.008), chronic kidney disease ( p = 0.025), and chronic hemodialysis ( p = 0.042) were significantly higher among the FM group. Sleep disorders, such as snoring and sleep apnea, were more prevalent among FM patients. The average sleep hours were significantly lower among the FM group ( p < 0.001). FM patients had statistically significantly lower scores across all domains of SF36. Conclusion FM is prevalent among Egyptian SLE patients, and shows significant associations with age, BMI, SLE duration and activity, and disturbed sleep pattern and has a negative impact on their HRQoL. Therefore, early detection and treatment are recommended.